Evidence for self‐association of the alternative sigma factor σ54. (11th February 2013) - Sabbatini, Massimo; Vezzoli, Alessandro; Milani, Mario; Bertoni, Giovanni
<x xml:space="preserve">Abstract</x> Sigma factor σ54 has a distinct modus operandi for mediating the activation of bacterial RNA polymerase (RNAP) at promoter recognition motifs 12 and 24 bp upstream from transcription start sites. σ54 was thought to act as monomer in all transcription steps. However, we provide evidence that σ54 of Pseudomonas putida interacts stably with itself. The interface between monomers involves contacts in σ54 regions I and III, sequences that play key roles in the transcription activation of σ54–RNAP holoenzyme. These roles include interactions with activator proteins and the −12 and −24 motifs. In particular, we detected inter‐monomer contacts between region I, and between region I and the C–terminal portion of region III. Our results suggest a new auto‐antagonistic regulatory state of σ54. Structured digital abstract σ54 and σ54 bind by molecular sieving (View Interaction: 1, 2) σ54 and σ54 bind by blue native page (View interaction) P. aeruginosa σ54 physically interacts with P. aeruginosa σ54 by two hybrid (View interaction) σ54 physically interacts with σ54 by two hybrid (View Interaction: 1, 2, 3) p53 physically interacts with SV40T by two hybrid (View interaction)